2010
DOI: 10.1007/s10787-010-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Drug-resistant tuberculosis: an insurmountable epidemic?

Abstract: Drug-resistant tuberculosis has brought back the spectre of pre-antibiotic days. WHO surveillance data from 2007 showed multi-drug-resistant tuberculosis (MDR-TB)-tubercle bacillus resistant to both isoniazid and rifampicin accounting for 4.8% of all new and subsequent cases of tuberculosis. India and China-the two most populated countries of the world, house the maximum number of drug-resistant tuberculosis cases. In eastern European and central Asian countries, more than 6% of new TB cases are MDR-TB, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…The emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) Mycobacterium tuberculosis strains has made the current treatments less efficient. Therefore, the development of new pharmacological strategies to fight this disease are urgently needed [1]. It has been shown that M. tuberculosis is able to store triacylglycerols (TAG) as intracellular lipid inclusions (ILI), in vivo , during the infection process [2], [3], [4], [5] and in vitro , under stress conditions [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) Mycobacterium tuberculosis strains has made the current treatments less efficient. Therefore, the development of new pharmacological strategies to fight this disease are urgently needed [1]. It has been shown that M. tuberculosis is able to store triacylglycerols (TAG) as intracellular lipid inclusions (ILI), in vivo , during the infection process [2], [3], [4], [5] and in vitro , under stress conditions [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Isoniazid alone resistance produces poor outcomes following treatment with standard TB regimens [14], and isoniazid is frequently used alone or in combination with antiretroviral therapy (ART) for the prevention of TB in HIV-infected subjects, [15–17]. HIV coinfection increases the risk of death by 50 percent among TB cases, [18] with an even higher risk in the presence of MDR-TB [19, 20]. In a study of TB drug resistance and mortality in Peru involving 287 TB patients, 17 of 31 (55%) HIV-MDR-TB patients died before the confirmation of their MDR-TB status [21].…”
Section: Introductionmentioning
confidence: 99%
“…в 2007 г.). Затем появился туберкулез с ШЛУ МБТ (ШЛУ туберкулез) [3][4][5][6][7], который до 2007 г. составлял около 10 % всех случаев туберкулеза с МЛУ МБТ [8]. ШЛУ туберкулез с МБТ распространен более чем в 45 странах, точные дан ные получить затруднительно, т. к. не во всех странах существуют специализированные бактериологичес кие лаборатории [9].…”
Section: обзорыunclassified